Errors and erasures decoding of BCH and Reed-Solomon codes for reduced M-ary orthogonal signaling. - Joiner, L.L.
The paper presents a comparison of communication systems using different signal constellation sizes and Reed-Solomon or Bose-Chaudhuri-Hocquengem codes with different rates so that the overall required bandwidth is the same for each system. In these comparisons, the channel symbol size is smaller than the code symbol size, so that a code symbol contains parts of multiple channel symbols. Thus, the normal assumption of independent code symbols does not apply. Instead, consideration must be taken to obtain the best arrangement of channel symbols in each code symbol. Analytical expressions are developed to compare the bit error probability performance of comparable systems, based on individual codewords using errors-only decoding and errors and erasures decoding with transmission over a Rayleigh fading channel.
Keywords: BCH codes; Bose-Chaudhuri-Hocquengem codes; DS-CDMA.; M-ary orthogonal signaling; RS codes; Rayleigh fading channel; Reed-Solomon codes; Bit error probability; Channel symbol size; Code symbol size; Communication systems; Constant bandwidth; Error control code; Errors and erasures decoding; Errors-only decoding; Signal constellation sizes